Clinico-epidemiological Profile of Rosacea at a Tertiary Care Hospital in Eastern Nepal - Bhattarai, S; Agrawal, S; Rijal, A (Nepal Journal of Dermatology, Venereology & Leprology, 2012)
DOI: http://dx.doi.org/10.3126/njdvl.v10i1.6420 NJDVL 2012; 10(1): 27-32